15.1k views
1 vote

\sqrt15-x +\sqrt3-x=6

1 Answer

6 votes

As currently written, solving for
x, we have


√(15) - x + \sqrt3 - x = 6


2x = √(15) + \sqrt3 - 6


x = \frac{√(15) +\sqrt3 - 6}2

I suspect you meant to write


√(15 - x) + √(3 - x) = 6

Move one of the roots to the other side, then take squares on both sides.


√(15 - x) = 6 - √(3 - x)


\left(√(15 - x)\right)^2 = \left(6 - √(3 - x)\right)^2


15 - x = 36 - 12 √(3 - x) + (3 - x)


12 √(3 - x) = 24

Take squares again


\left(12√(3-x)\right)^2 = 24^2


144 (3 - x) = 576


432 - 144x = 576


144x = -144


\boxed{x = -1}

User Stroblme
by
6.1k points